Structural analysis of minimum wage rates, unemployment and food prices of farm workers in South Africa: co-Integration approach - Lekunze, Joseph Nembo; Luvhengo, Usapfa; Shoko, Rangarirai Roy (Uniwersytet Przyrodniczy w Poznaniu, 2016)
This paper examines the short- and long- term effects of increasing minimum wage rates for farm workers in South Africa on structural unemployment and rising food prices in the economy. The Pearson correlation model was used to establish association between variables. Analysis found a negative association (-0.651) between wage rate and employment of farm workers, while a positive (0.021) association was found to exist between wage rate (W) increases and food prices (Fp). No association (0.001) was found between employment and food prices (Fp). Co-integration was further employed to determine the short-term and long-term relationships, and the analysis found wages to have a positive and signifi cant (0.453) eff ect on structural unemployment of farm workers. Unemployment was observed to be wage elastic in the long term and wage inelastic in the short term. The long-term relationship showed increasing unemployment in agriculture (L) and rising food prices (Fp) (1.168), while the short-term relationship showed a signifi cant error correction coeffi cient (ECT) with an expected starting point of 41.9% adjustment rate towards long-term equilibrium within a year. Structural analysis confi rmed an inelastic demand for basic food. The study suggest government subsidies to farmers through cost-cutting technologies and farm worker's skills development on the use of these technologies.
Keywords: Minimum wage; unemployment of farm workers; food prices; structural change